Novel H7N2 and H5N6 Avian Influenza A Viruses in Sentinel Chickens: A Sentinel Chicken Surveillance Study - Zhao, Teng; Qian, Yan-Hua; Chen, Shan-Hui; Wang, Guo-Lin; Wu, Meng-Na; Huang, Yong; Ma, Guang-Yuan; Fang, Li-Qun; Gray, Gregory C.; Lu, Bing; Tong, Yi-Gang; Ma, Mai-Juan; et al. (Frontiers in Microbiology, 2016)
In 2014, surveillance of sentinel chicken for avian influenza virus was conducted in aquatic bird habitat near Wuxi City, Jiangsu Province, China. Two H7N2, one H5N6, and two H9N2 viruses were isolated. Sequence analysis revealed that the H7N2 virus is a novel reassortant of H7N9 and H9N2 viruses and H5N6 virus is a reassortant of H5N1 clade 2.3.4 and H6N6 viruses. Substitutions V186 and L226 (H3 numbering) in the hemagglutinin (HA) gene protein was found in two H7N2 viruses but not in the H5N6 virus. Two A138 and A160 mutations were identified in the HA gene protein of all three viruses but a P128 mutation was only in the H5N6 virus. A deletion of three and eleven amino acids in the neuraminidase stalk region was found in two H7N2 and H5N6 viruses, respectively. Moreover, a mutation of N31 in M2 protein was observed in both two H7N2 viruses. High similarity of these isolated viruses to viruses previously identified among poultry and humans, suggests that peridomestic aquatic birds may play a role in sustaining novel virus transmission. Therefore, continued surveillance is needed to monitor these avian influenza viruses in wild bird and domestic poultry that may pose a threat to poultry and human health.